Аналіз умов виникнення та змагальної діяльності лижних марафонів Visma Ski Classics - Andrii Kazmiruk; Olexandr Chenikalo; Olha Zinkiv; Yurii Liubizhanin (Lesya Ukrainka Volyn National University, 2022)
The article highlights the historical aspects of the formation, features and prerequisites for the emergence of new disciplines in ski racing on the example of the Visma Ski Classics. Purpose of the Research is to analyze the reasons for the emergence and features of the competitive activity of Visma Ski Classics. Stuff and Methods of the Research. Achieving the goal was ensured by using a number of general scientific research methods. In particular, the analysis and synthesis of theoretical data was chosen because they allowed to describe a relatively wide range of issues in a more diverse way. The information relating to various aspects of the preconditions for the emergence of Visma Ski Classics has been taken into account. Results of the Research. Based on a detailed analysis of scientific and methodological sources and available information on the Internet, it was established that Visma Ski Marathon was based on the stages of the Tour de Ski multi-day skiing competition. The basis for which, in its turn, were multi-day cycling competitions, namely Tour de France. This is a positive component in the development and popularization of ski racing, because it, like most winter sports, is a conservative sport. The modern world requires dynamic changes; so many commercial starts began to appear. One of them is a series of Visma Ski Classics. The article features 12-season history of the marathons, the peculiarities of rules and regulations and highlights the events of the last season, namely the weather conditions, Covid pandemic and the war in Ukraine and how it affected the course of the competitions. Findings. On the whole, authors view Visma Ski Classics marathons as a positive trend in the development of cross-country skiing as they enable wide range of people to enjoy this kind of sport.